Transforming the Academy : Faculty Perspectives on Diversity and Pedagogy - Willie-LeBreton, Sarah, 1963- (Book collections on Project MUSE., 2016)
Transforming the Academy brings together faculty members from many different backgrounds-male and female, cisgender and queer, immigrant and native-born, white, black, multiracial, and other-to examine the state of diversity within the American university. Whether describing challenging power dynamics within their classrooms or recounting protests that occurred on their campuses, the book's contributors offer bracingly honest inside accounts of both the conflicts and the learning experiences that can emerge from being a representative of diversity.